2015
DOI: 10.1038/srep09691
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Two-Photon Imaging of Axonal Dieback, Blood Flow and Calcium Influx withMethylprednisolone Therapy after Spinal Cord Injury

Abstract: Severe spinal cord injury (SCI) can cause neurological dysfunction and paralysis. However, the early dynamic changes of neurons and their surrounding environment after SCI are poorly understood. Although methylprednisolone (MP) is currently the standard therapeutic agent for treating SCI, its efficacy remains controversial. The purpose of this project was to investigate the early dynamic changes and MP's efficacy on axonal damage, blood flow, and calcium influx into axons in a mouse SCI model. YFP H-line and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 61 publications
0
43
0
1
Order By: Relevance
“…Transection paradigms include, for example, dorsal hemisection at the lower thoracic level using a microknife (Tedeschi et al, ) or at the cervical level with a 3.8‐mm‐wide piece of razor blade (Onifer et al, ), lateral hemisection at the T11–12 level using microscissors (Tang et al, ) and DC transection at the high cervical level with a Scouten wire‐knife (Hollis et al, ). In demonstrating the CL effect in a DC lesion, a bilateral complete DC transection up until the central canal was used (Neumann and Woolf, ), also severing the descending CST in rats.…”
Section: Experimental Lesion Models For Dorsal Column Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Transection paradigms include, for example, dorsal hemisection at the lower thoracic level using a microknife (Tedeschi et al, ) or at the cervical level with a 3.8‐mm‐wide piece of razor blade (Onifer et al, ), lateral hemisection at the T11–12 level using microscissors (Tang et al, ) and DC transection at the high cervical level with a Scouten wire‐knife (Hollis et al, ). In demonstrating the CL effect in a DC lesion, a bilateral complete DC transection up until the central canal was used (Neumann and Woolf, ), also severing the descending CST in rats.…”
Section: Experimental Lesion Models For Dorsal Column Injurymentioning
confidence: 99%
“…Fluorescent proteins can also be expressed using transgenic mouse lines, such as the Thy1‐GFP‐M (Tedeschi et al, ), ‐YFP (He et al, ), or ‐GCaMP (Tang et al, ) lines, providing fluorescent labeling of DRG neuron without the need for surgical intervention, although expression is not limited to these neurons and not specific for particular DRG. This approach has been used, for example, for two‐photon time‐lapse imaging to monitor changes in axonal networks in living mice (Dray et al, ; Farrar et al, ; Lorenzana et al, ; Tang et al, ).…”
Section: Assessment Of Regeneration and Functional Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Bei Tang et al war 3 Tage nach Trauma die Anzahl der entzündungsvermittelnden aktivierten Mikroglia/Makrophagen signifikant in der Kontrollgruppe erhöht. Eine quantitative Analyse von proinflammatorischen Faktoren, 3 Tage nach SCI, zeigte hingegen eine signifikante Erniedrigung von iNOS (10,3-fach), MCP-1 (3,6-fach) und IL-1 (4,9-fach), im Vergleich zur Kontrollgruppe [25]. Somit scheint, zumindest im Tierversuch, eine MPSS-Gabe das funktionelle Outcome nach SCI zu verbessern.…”
Section: Pathophysiologie Der Peripheren Nervenverletzungunclassified
“…The importance of calpain has been supported by experiments demonstrating that the application of the calpain inhibitor calpeptin blocks the formation of a new growth cone following injury (Gitler and Spira, ; Spira et al, ). In the vertebrate system, an early Ca 2+ influx also occurs in response to the injury during acute axonal degeneration, forming a gradient of Ca 2+ with the highest concentration near the injury site that is sustained over several hours (Stirling et al, ; Williams et al, ; Tang et al, ; Zhang et al, ). Studies have shown that neuronal recovery after injury is correlated with the Ca 2+ influx (Williams et al, ) and that limiting influx during acute axonal degeneration promotes neuronal survival and axon regeneration (Ribas et al, ).…”
Section: Introductionmentioning
confidence: 99%